The Comparison Of Antibacterial Effects On Cinnamomum Burmannii Water Extract With Penicillin Against Staphylococcus Aureus In Vitro - Halim, Felicia; Dewi, Bernadette Dian Novita; Sutandhio, Silvia (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Along with the development of science, many varieties of microorganisms are resistant to antibiotics. To avoid cases of resistance grew severe, researchers developed alternative medicines as a substitute for antibiotics. One of the ingredients of herbs researched that has antibacterial activity is Cinnamon (Cinnamomum burmannii). Aim: This study aimed to compare antibacterial effects water extract of Cinnamomum burmannii with penicillin against Staphylococcus aureus Methods: This an experimental studies witd non-equivalent control group design. Research using the bacteria S. aureus are divided into two groups, the control group and experimental group. The concentration of Cinnamomum burmannii and penicillin are used that is 80- 150mg/L. Antibacterial test used dilution method and a microplate reader for reading absorbance. This research conducted in the laboratory of Microbiology, Faculty of Pharmacy Widya Mandala Catholic University Surabaya for 2 weeks. Result: Based on visual observations, Cinnamomum burmannii’s MIC is located at concentration 320- 600 mg/L while penicillin’s MIC is located at concentration 160- 300 mg/L. Based on the results of microdilution test, Cinnamomum burmannii’s MIC is located at concentration 160- 300 mg/L while penicillin’s MIC is located at concentration 640- 1200 mg/L. Conclusion: The conclusion of this research is giving Cinnamomum burmannii water extract in Staphylococcus aureus has efficacy or inhibitory that is not significantly different with penicillin.